2019
DOI: 10.1111/bjir.12468
|View full text |Cite
|
Sign up to set email alerts
|

Pay and Job Rank among Academic Economists in the UK: Is Gender Relevant?

Abstract: This article presents and explores a rich new data source to analyse the determinants of pay and job rank among academic economists in the UK. Characteristics associated with individual productivity and workplace features are found to be important determinants of the relative wage and promotion structure in this sector. However, there is also a substantial unexplained gender pay gap. Men are considerably more likely to work in higher paid job ranks where there are also substantial within‐rank gender pay gaps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
(124 reference statements)
3
16
1
Order By: Relevance
“…We exploit high quality administrative data for the population of academics to paint the first comprehensive picture of the status of women in academic economics departments in research-intensive ("Russell Group" 2 ) universities in the UK. This builds on recent survey evidence suggesting that women in economics are under-represented, and are paid less than their male counterparts in the UK even after accounting for socio-demographic, worksplace, and productivityrelated characteristics (Mumford and Sechel, 2019). Our study is complementary to Auriol et al 1 In focusing on gender, we are not assuming that this is the only important dimension for diversity.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We exploit high quality administrative data for the population of academics to paint the first comprehensive picture of the status of women in academic economics departments in research-intensive ("Russell Group" 2 ) universities in the UK. This builds on recent survey evidence suggesting that women in economics are under-represented, and are paid less than their male counterparts in the UK even after accounting for socio-demographic, worksplace, and productivityrelated characteristics (Mumford and Sechel, 2019). Our study is complementary to Auriol et al 1 In focusing on gender, we are not assuming that this is the only important dimension for diversity.…”
Section: Introductionmentioning
confidence: 81%
“…We do not have any information on children, which have been shown to affect earnings, nor direct measures of productivity, but we include variables that are correlated with productivity in the literature, i.e. age and age squared to proxy for experience, and employment characteristics such as tenure, tenure squared and a part-time indicator (Mumford andSechel, 2019 andBlackaby, at al, 2005). Panel B in Table 3 shows all the summary stats for these variables for each discipline, and Table A3 in Appendix A describes how these variables are constructed.…”
Section: Iiiii Gender Pay Gapsmentioning
confidence: 99%
“…While there is robust data on gender pay gaps in academia 13 , our study only examined gaps specifically in biomedical sciences. Our study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…While there is an expanding body of literature on pay gaps in of academia and of medicine in general 9 , 13 , there is currently very limited literature that evaluates how journal editors are compensated for their work. An international email survey of 88 editors of nursing journals found that their mean annual salary was $12,749 USD (ranging from $0 to $56,000) for a mean of 13.4 hours worked per week 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This may no longer be the case if women are now forming similar workplace expectations to men (Green et al, 2018). Recent studies also highlight a range of gender inequities in the Economics discipline (Lundberg and Stearns, 2018;Mumford and Sechel, 2019) that might reasonably alienate females and lower their job satisfaction (Ceci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%